2014
DOI: 10.12691/ijdsr-2-6-13
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Facial Measurements and Occlusal Vertical Dimension: An Anthropometric Study in Two Ethnic Groups of Nepal

Abstract: Establishment of proper occlusal vertical dimension is the important yet daunting task for successful prosthodontic therapy for function, esthetics and comfort to the edentulous patients. In the current study the relationship of various distances between facial landmarks to the OVD was tested in two ethnic groups of Nepal, viz. Aryans and Mongoloids. The result of this study can be useful in determining proper OVD in the patients who have lost the OVD. The aim of the study was to find the correlation between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…This correlation was higher, with higher significant level, between the pair (eye-RO) and (N-Gn) than that between (eye-RO) and (Sn-Me). Although these findings seem to be consistent with those found by Nagpal et al .,[ 21 ] Delic et al .,[ 22 23 ] and Basnet et al .,[ 24 ] they differ from a study conducted by Tina-Olaivar et al . [ 25 ] in which he found that the difference between (eye-RO) and (N-Gn) was 3 cm, this variation might be because their study was carried out on Mongoloid individuals while this study was conducted on Caucasian subjects.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This correlation was higher, with higher significant level, between the pair (eye-RO) and (N-Gn) than that between (eye-RO) and (Sn-Me). Although these findings seem to be consistent with those found by Nagpal et al .,[ 21 ] Delic et al .,[ 22 23 ] and Basnet et al .,[ 24 ] they differ from a study conducted by Tina-Olaivar et al . [ 25 ] in which he found that the difference between (eye-RO) and (N-Gn) was 3 cm, this variation might be because their study was carried out on Mongoloid individuals while this study was conducted on Caucasian subjects.…”
Section: Discussioncontrasting
confidence: 56%
“…Differences in the distance (between the outer canthus of the eye and parting of the lips) as well as (from tip of the nose to tip of the chin) between males and females were significant. Similar differences between the genders were described by Nagpal et al .,[ 21 ] Delic et al .,[ 22 23 ] Basent et al .,[ 24 ] and Al-Hamdany. [ 26 ] It is somewhat surprising that no significant differences were found in the current study between males and females regarding the distance from the septum of the nose to the under of the chin.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, N‐Gn distance was suggested as a tool to measure the OVD. Basnet et al . carried out a study to compare different craniofacial measurements against N‐Gn distance in two ethnic groups of Nepal.…”
Section: Post‐extraction Methodsmentioning
confidence: 99%
“…Alternatively, N-Gn distance was suggested as a tool to measure the OVD. Basnet et al (98) carried out a study to compare different craniofacial measurements against N-Gn distance in two ethnic groups of Nepal. The results showed that all the four measurements (pupil-rima oris, eye-ear, ear height, outer canthus of the eye-inner canthus of the other eye) were significantly correlated with N-Gn distance.…”
Section: Craniofacial Landmarks Measurementsmentioning
confidence: 99%
“…6 The mechanical method such as jaw relationmethods and recording pre-extraction methods that classified into three methods: radiographic profile,study casts, and facial measurement.Various methods of measuring faces with different gauge in determining the vertical dimension has been introduced, such as Sorrenson's method that uses Sorrenson's profile scale, Mc.Gee methods that use a ruler bending, Willis method that uses Willis's gauge, Interpupillary distance's method, dan Ear-eye distance method. 7,11,12 These methods are continue to study their suitability of different races.…”
Section: Introductionmentioning
confidence: 99%